ANALYTICAL CALCULATION AND EXPERIMENTAL RESEARCH ON THE BEARING CAPACITY OF FAN-SHAPED HYDROSTATIC THRUST BEARING SUPPLIED WITH CONSTANT OIL FLOW - WANG ShaoLi; XIONG WanLi; MENG ShuGuang; GUI Lin; XUE JingYu; FU MaLi (Jixie qiangdu, 2015)
In the traditional design method of heavy duty hydrostatic rotary table,the influence of centrifugal force has not been considered in the calculation of bearing capacity of fan-shaped hydrostatic thrust bearing supplied with constant oil flow and the adopted simplified calculation method is lack of experimental verification.In this paper,a new analytical calculation method of bearing capacity of fan-shaped hydrostatic thrust bearing supplied with constant oil flow is presented in which the influence of centrifugal force is considered.The experimental system of heavy duty hydrostatic rotary table is designed and established,and corresponding experiment is carried out.The experimental results have a good fitness with analytical calculated ones,which has verified the validity of the proposed calculation method.The new method provides a theoretical basis for the design and calculation of the fan-shaped hydrostatic thrust bearing supplied with constant oil flow.